1995
DOI: 10.1038/sc.1995.56
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of spinal injuries from diving in Slovenia

Abstract: Injury of the cervical spine involving the spinal cord such as results from diving into shallow water causes very severe disability. In spite of progress in medical science, results of the treatment and rehabilitation of such patients are not satisfactory. Every effort should be undertaken to give young swimmers, the most frequent victims of diving injuries, proper instructions to prevent spinal cord injury. A broadly conceived national prevention programme, developed under the catch-phrase 'Do Not Jump into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
0
14
0
3
Order By: Relevance
“…The usual type of injury found in most studies appears to result from compression, suggesting that injuries occur when the person's head hits the bottom of the pool. 13,14,17,25 However, Kewalramani et al found diving injuries resulted in only 20% burst fractures and 80% wedge or teardrop fractures, indicating¯exion type injuries that they believe occur on impact with the water rather than the bottom of the pool. 18,19 In the current study, information on the mechanism of injury was not collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usual type of injury found in most studies appears to result from compression, suggesting that injuries occur when the person's head hits the bottom of the pool. 13,14,17,25 However, Kewalramani et al found diving injuries resulted in only 20% burst fractures and 80% wedge or teardrop fractures, indicating¯exion type injuries that they believe occur on impact with the water rather than the bottom of the pool. 18,19 In the current study, information on the mechanism of injury was not collected.…”
Section: Discussionmentioning
confidence: 99%
“…These demographic ®ndings are consistent with several other studies of SCI resulting from diving mishaps. 14,16,18,22 Educational interventions might be coordinated with local school systems to increase awareness of the potential risks and safety precautions to minimize those risks. The educational message might focus on becoming familiar with the pool and making sure the depth of the pool is known before diving, avoiding alcohol when using swimming pools, not using pools during darkness, teaching proper diving technique, being careful about trying unusual types of dives, and not using the pool alone.…”
Section: Discussionmentioning
confidence: 99%
“…Die Frequenz derartiger Verletzungen ist regional stark unterschiedlich, bildet die Ausnahme in Slowenien [6] und beträgt 78% in den USA [8]. Die Frequenz derartiger Verletzungen ist regional stark unterschiedlich, bildet die Ausnahme in Slowenien [6] und beträgt 78% in den USA [8].…”
Section: Diskussionunclassified
“…Studies looking at the prevention of diving accidents lay emphasis on education, and raising awareness of the dangers of negligence and reckless behavior in swimming pools [4,7,8,15]. Important advice includes ''don't dive into unfamiliar water'', ''don't permit or indulge in horseplay while swimming or diving'', ''link hands with the arms extended in the diving position'', and ''don't dive in water less twice your height''.…”
Section: Preventionmentioning
confidence: 99%